PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH - Pratiwi, Ni Putu Lenny; Seminari, Ni Ketut (E-Jurnal Manajemen, 2015)
Creating customer satisfaction, especially customers, cooperatives should be able to meet the wishes of the customer. Factors that affect customer satisfaction is service quality , trust and customer value . This study aims to investigate the influence of service quality , trust and customer value partially on customer satisfaction. Respondents in this study is the chairman of the cooperative and 98 clients , with non- probability sampling technique is purposive sampling . The data analysis technique used is the technique of multiple linear regression analysis . The results obtained by analysis of the conclusion that the partial test results can be known service quality , trust and customer value and significant positive effect on customer satisfaction on Credit Unions Dauh Ayu Denpasar .
Keywords: quality of service , trust , customer value and satisfaction